When Your Attorney is Your Enemy: Preliminary Thoughts on Ensuring Effective Representation for Queer Youth - Valentine, Sarah (Columbia Journal of Gender and Law, 2010)
Attorneys representing children too often become their enemies rather than their advocates. This is especially true when the children are queer. Queer youth caught in the judicial system are often severely harmed, specifically because of where a court decides they will reside. Judges determine where children will reside through custody decisions, or by deciding whether they will be placed in foster care, group homes, or detention facilities in child welfare and delinquency proceedings. Once in the justice system, most children are provided an attorney in part because courts have recognized that children have a liberty interest at stake in the proceedings, including a right to “reasonably safe living conditions” and services necessary to ensure protection from harm. Where a child will be placed is always an important issue in cases involving juveniles and thus a pivotal issue for the child’s attorney. However, for queer children, questions of placement are critical, because they can have terrible, even life-threatening, consequences.